The Relationship between Hygiene Behaviour and Acne Vulgaris Incidence in Medical Students Sebelas Maret University - Hapsari, Jasmine Rahmi; Murasmita, Alamanda; Widhiati, Suci; Kusumawardani, Arie (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2022)
Background: Hygiene behaviour is a person's actions in maintaining cleanliness to prevent the spread of infectious disease by cutting off the transmission of microorganisms that cause infection both in the community and in the health service. Various diseases caused by poor hygiene behaviour are diarrhea, dengue fever, leptospirosis, acute respiratory tract infections, typhoid fever, and various skin infections. One of the infectious skin diseases that affects almost the entire population is acne vulgaris. It is the highest disease prevalence worldwide and ranked 8th with 645.499.139 sufferers. Purpose: To determine the relationship between hygiene behaviour and acne vulgaris incidence in medical students at Sebelas Maret University. Methods: This study was an observational analytical study with a cross-sectional approach. This study was conducted on 45 male medical students at Sebelas Maret University. The questionnaire used was Hygiene Inventory (HI23). Data were analyzed using Fisher's Exact correlation test. Result: There is no relationship (p = 0.720) between hygiene behaviour and acne vulgaris incidence in medical students of the Sebelas Maret University. Conclusion: Hygiene behaviour has no relationship with acne vulgaris incidence in medical students at Sebelas Maret University.